2016
DOI: 10.1155/2016/7546265
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Oxidative Stress Related Genes in a Chronic Kidney Disease Attributed to Specific Geographical Locations of Sri Lanka

Abstract: Objective. To infer the influence of internal and external oxidative stress in chronic kidney disease patients of unknown etiology (CKDu) in Sri Lanka, by analyzing expression of genes related directly or indirectly to oxidative stress: glutamate-cysteine ligase catalytic subunit (GCLC), glutathione S-transferase mu 1 (GSTM1), glucose-6-phosphate dehydrogenase (G6PD), fibroblast growth factor-23 (FGF23), and NLR family pyrin domain containing 3 (NLRP3). Methods. Reverse transcription quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Up regulation of the GCLC and GSTM1 genes in the Girandurukotte healthy population compared to Kandy healthy population has been documented in a separate cohort [51] and has been hypothesized to be due to the environmental oxidative stressors that the population may be exposed to. These genes therefore hold potential as early screening markers, but needs further follow-up and testing.…”
Section: Discussionmentioning
confidence: 99%
“…Up regulation of the GCLC and GSTM1 genes in the Girandurukotte healthy population compared to Kandy healthy population has been documented in a separate cohort [51] and has been hypothesized to be due to the environmental oxidative stressors that the population may be exposed to. These genes therefore hold potential as early screening markers, but needs further follow-up and testing.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study was conducted to assess gene expression changes associated with oxidative stress in CKD and CKDu patients in comparison to healthy controls from CKDu endemic and non-endemic areas. Compared to the controls from non-endemic areas, genes coding for glutamate-cysteine ligase catalytic subunit (GCLC), glutathioneS-transferasemu1 (GSTM1), fibroblast growth factor-23 (FGF23), and NLR family pyrin domain containing 3 (NLRP3) were upregulated in CKD and CKDu patients in varying degrees [ 83 ]. These studies indicate that redox imbalance may play a mechanistic role in initiation or progression of this disease, and oxidative stress markers may serve as early biomarkers of renal cellular dysfunction.…”
Section: Current Use Of Novel Biomarkers In Ckdu Hotspots and Theimentioning
confidence: 99%
“…Notably, while KIM-1 and NGAL remain more widely used in higher income countries, clinical use of these markers remain novel in the clinical settings of low-middle income countries. Recently, a few comparative studies in Sri Lanka have demonstrated the applicability of several novel biomarkers along with conventional markers in CKDu screening [11,12,17]. To date a comprehensive assessment of novel biomarkers in communities with diverse occupational and socioeconomic strata in different climatic zones has not been performed in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%